Reduction in lower-alpha power during Ganzfeld flicker stimulation is associated with the production of imagery and trait positive schizotypy. (December 2018) - Sumich, Alex; Anderson, John D.; Howard, Christina J.; Heym, Nadja; Castro, Antonio; Baker, Joshua; Belmonte, Matthew K.
Abstract: Light-flicker Ganzfeld (LFG) induces a lower to upper-alpha frequency shift. However, it is unclear how this neurophysiological response might relate to LFG-induced pseudo-hallucinatory phenomena. It is also unknown whether emotional states (e.g., fear) or traits associated with risk for psychosis (e.g., proneness to perceptual anomalies, ability to produce vivid mental imagery) affect such neurophysiological and/or perceptual responses to LFG. The present study investigated alpha sub-bands during LFG across several flicker frequencies, in relation to individual differences in propensity for Ganzfeld-induced imagery (GI), positive schizotypy and trait mental imagery, and in relation to manipulations of affective state. Given previously reported sex differences in risk for psychosis and response to Ganzfeld, the effect of sex on GI was also studied. Forty-six healthy adults (16 men) completed psychometric measures of trait mental imagery and positive schizotypy before undergoing three LFG (20 min each) conditions. In each condition, participants wore white-out goggles and listened to either mood-inducing soundscapes (fear, serenity) or pink noise (control) through headphones. Greatest propensity for GI arose between 13.1 and 16.0 Hz flicker, with a peak at 16.0 Hz flicker. Occipital lower-alpha was reduced for lower flicker frequencies (13.1–16.0 Hz) and was inversely associated with GI. Upper-alpha power was not significantly related to GI or to other measures. Fear-induction was associated with reduction in alpha power, but did not significantly affect GI. Men reported more GI than women. Findings support a role for cortical destabilisation, as reflected in reduced lower-alpha, in perceptual anomalies; and, by extension, LFG as an experimental model of liability for psychosis. Highlights: 12–16 Hz flicker induces less lower-alpha power and evokes more Ganzfeld imagery compared to 20–24 Hz flicker. Lower-alpha power inversely correlates with reported Ganzfeld imagery and schizotypy. Fear induction is related to reduction in alpha power, but not increased imagery. Men experience more Ganzfeld imagery than women.